1985
DOI: 10.1682/jrrd.1985.07.0018
|View full text |Cite
|
Sign up to set email alerts
|

Walking casts : effect on plantar foot pressures

Abstract: -Pressure measurements were made at four sites on the right foot of six normal subjects while they walked in a standard shoe, conventional padded cast, total contact cast, and again in a shoe . No differences in mean relative pressure were found between the padded cast and the total-contact cast. Significant reductions in mean relative pressure were found between the standard shoe and walking casts at the first and third metatarsal head . This study supported the use of walking casts in the management of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 10 publications
(6 reference statements)
0
16
0
1
Order By: Relevance
“…23 Subjects lacked protective sensation if they could not detect the 5.07 monofilament on 80% of the trials. 28 Stiffness measurements. In order to verify that the stiffness measurements were truly passive (no active muscle contractions elicited), electromyographic (EMG) monitoring (GCS-67 Multichannel Electromyographic System*) was used throughout the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Subjects lacked protective sensation if they could not detect the 5.07 monofilament on 80% of the trials. 28 Stiffness measurements. In order to verify that the stiffness measurements were truly passive (no active muscle contractions elicited), electromyographic (EMG) monitoring (GCS-67 Multichannel Electromyographic System*) was used throughout the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral neuropathy was characterized by the loss of protective sensation on the plantar surface of the foot, measured using Semmes-Weinstein monofilaments. 28 Exclusion criteria consisted of a current or previous severe orthopedic injury to the lower extremity (eg, ankle fracture, joint fusion, joint replacement) or a current or previous neurological insult (eg, cerebrovascular accident).…”
Section: Subjectsmentioning
confidence: 99%
“…TCC has also been shown to reduce forefoot pressure and facilitate wound healing. 4 The ankle joint was casted in a neutral position throughout the immobilization period. Once dry, the TCC was bivalved to allow for swelling.…”
Section: Tendo-achilles Lengthening Procedures and Treatmentmentioning
confidence: 99%
“…Brike JA et al 16 reported a 75% to 84% reduction in peak pressure at the 1st and 3rd metatarsal heads respectively, when a person walked in the total contact cast compared to normal shoes. Therefore, the utility of contact-casting is in reducing peak plantar pressures, through increasing the surface area of the foot.…”
Section: Discussionmentioning
confidence: 99%